"It's better language": The social meanings of academic language in an elementary classroom. Issue 2 (3rd April 2022) - Corella, Meghan
ABSTRACT: Despite an increased interest in academic language in recent years, critical and sociopolitical perspectives in this area of scholarship remain scarce. This paper presents brings such perspectives to the study of academic language by proposing a framework that highlights its situated social meanings through a focus on social identities and language ideologies. An ethnographically informed discourse analysis of a second-grade student's interactions with peers and adults shows how she used language locally understood as "academic" as a resource for positioning herself as authoritative, intellectually able, and appropriately behaving. Her constructions of these identities tended to reproduce hegemonic ideologies of language, class, race, gender, sexuality, the body, and emotionality, although at times her practices unsettled other dominant discourses, such as adult–child hierarchies. The theoretical and pedagogical implications of these findings and the proposed framework are discussed, with an emphasis on the need for critical language scholars and educators to continue countering oppressive language ideologies by attending to the social meanings of academic language.